The Cross-Education Phenomenon: Brain and Beyond - Hendy, Ashlee M.; Lamon, Séverine (Frontiers in Physiology, 2017)
Objectives: Unilateral resistance training produces strength gains in the untrained homologous muscle group, an effect termed ‘cross-education’. The observed strength transfer has traditionally been considered a phenomenon of the nervous system, with few studies examining the contribution of factors beyond the brain and spinal cord. In this hypothesis and theory article, we aim to discuss further evidence for structural and functional adaptations occurring within the nervous, muscle and endocrine systems in response to unilateral resistance training. The limitations of existing cross-education studies will be explored, and novel potential stakeholders that may contribute to the cross-education effect will be identified. Design: Critical review of the literature. Method: Search of online databases. Results: Studies have provided evidence that functional reorganization of the motor cortex facilitates, at least in part, the effects of cross-education. Cross-activation of the ‘untrained’ motor cortex, ipsilateral to the trained limb, plays an important role. While many studies report little or no gains in muscle mass in the untrained limb, most experimental designs have not allowed for sensitive or comprehensive investigation of structural changes in the muscle. Conclusions: Increased neural drive originating from the ‘untrained’ motor cortex contributes to the cross-education effect. Adaptive changes within the muscle fiber, as well as systemic and hormonal factors require further investigation. An increased understanding of the physiological mechanisms contributing to cross-education will enable to more effectively explore its effects and potential applications in rehabilitation of unilateral movement disorders or injury.